Emotional intelligence on student’s aggressive behavior with early childhood education background - Nurmailis, Nurmailis; Dewi, Muhtiarti Rahmi; Dona, Rahma (Program Studi bimbingan Konseling PPs UNM Makassar, 2024)
This study investigates the impact of emotional intelligence on aggressive behavior among high school students in Depok who have previously experienced early childhood education (PAUD). Employing a quantitative approach with a simple linear regression design, a sample of 446 high school students in Depok was selected through purposive sampling. Emotional intelligence was assessed using a Likert scale questionnaire consisting of 22 items, demonstrating a reliability coefficient of 0.833, while aggressive behavior was evaluated with a reliability coefficient of 0.833 across 25 items. Descriptive analysis revealed that the mean score for emotional intelligence (65.74) surpassed that of aggressive behavior (56.39), suggesting that higher levels of emotional intelligence may serve as a mitigating factor against aggressive tendencies. Regression analysis further illustrated a significant impact, yielding an R-square value of 0.984 and a p-value of 0.000 (< 0.05), indicating that 98,4% of emotional intelligence contributes to aggressive behavior.